2008
DOI: 10.1002/bdrc.20118
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and brain development

Abstract: Preclinical studies, using primarily rodent models, have shown acetylcholine to have a critical role in brain maturation via activation of nicotinic acetylcholine receptors (nAChRs), a structurally diverse family of ligand-gated ion channels. nAChRs are widely expressed in fetal central nervous system, with transient upregulation in numerous brain regions during critical developmental periods. Activation of nAChRs can have varied developmental influences that are dependent on the pharmacologic properties and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
180
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(193 citation statements)
references
References 147 publications
4
180
0
4
Order By: Relevance
“…In a recent study, PNE was reported to reduce the cingulate cortex volume in mice (Zhu et al, 2012), as observed in AD/HD subjects (Makris et al, 2010), implying that the reduced thickness of cortical layers may be associated with the decrease in cell number induced by PNE. In addition, previous studies have demonstrated that nAChRs including α4β2 and α7 are expressed in progenitor cells in embryonic mouse brain (Dwyer et al, 2008). These studies support our present findings that α7 nAChRs mediate the decreased proliferation of neuronal progenitors by PNE in the VZ and SVZ layers on E14 (Figure 2 and Supplementary Figure S1).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a recent study, PNE was reported to reduce the cingulate cortex volume in mice (Zhu et al, 2012), as observed in AD/HD subjects (Makris et al, 2010), implying that the reduced thickness of cortical layers may be associated with the decrease in cell number induced by PNE. In addition, previous studies have demonstrated that nAChRs including α4β2 and α7 are expressed in progenitor cells in embryonic mouse brain (Dwyer et al, 2008). These studies support our present findings that α7 nAChRs mediate the decreased proliferation of neuronal progenitors by PNE in the VZ and SVZ layers on E14 (Figure 2 and Supplementary Figure S1).…”
Section: Discussionsupporting
confidence: 92%
“…In the developing brain, nAChRs have been implicated in neuronal proliferation, apoptosis, migration, and differentiation (Dwyer et al, 2008(Dwyer et al, , 2009. Accordingly, nicotine is likely to affect these processes during neurodevelopment, depending on the dose, developmental stage, and tissue or cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation is that prenatal tobacco exposure directly affects brain development through nicotine, which has been demonstrated in animal studies (Dwyer et al, 2008). For example, a thinner somatosensory cortex in rats has been demonstrated (Roy and Sabherwal, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…24 The a3b4 subtype is predominantly peripheral, but is also found in adult rat hippocampus 25 where it contributes to nicotine-evoked NE release from rat hippocampal synaptosomes. 26 27 The a4b2 and a3b4 nAChR subtypes selectively gate Na Ăľ , whereas a7 nAChRs have a higher ratio of Ca 2Ăľ to Na Ăľ permeability.…”
Section: Discussionmentioning
confidence: 99%